Smart Contracts for Ethical and Resilient Food Industry Logistics - Balaji Gopalan; Vijaya G S; Ravishankar Ulle (Logistic and Operation Management Research (LOMR), 2026)
The integration of smart contracts is transforming logistics and supply chain management (LSCM) by improving transparency, visibility, and accountability. This study examines how automated digital agreements and secure nutritional labeling enhance credibility and safety in the food industry. Using encrypted ledgers and records, smart contracts help address challenges such as counterfeit products, fraudulent labeling, and ethical violations. The study aimed to evaluate smart contracts as a strategic tool for managing information throughout a food product’s lifecycle, with emphasis on sustainability and ethical LSCM practices. A quantitative methodology was used, collecting survey data from 130 urban consumers in India who shop both online and offline. The survey captured consumer views on ethical consumption, organic versus processed foods, eco-friendly packaging, and pricing transparency. Findings show that although smart contracts are still emerging in the food sector, they can address major systemic issues. By defining accountability measures, these contracts can align societal well-being with industrial efficiency. This paper contributes to supply chain management research by highlighting the shift toward distributed information systems and emphasizing the importance of smart contracts in creating a transparent, ethical, and safe food supply chain for modern consumers.